(untitled) (SCHOLARS: Journal of Arts & Humanities, 2026)
The traumatic experiences of sexual abuse affect the lives of the victims in every possible way. Yet, within these experiences, the victims also emerge with a natural and sometimes a geographically shaped phenomenon to reconcile and reconstruct their lives, showcasing a framework of resilience. Both South Asian novels, Anuradha Roy’s Sleeping on Jupiter (2015) and Fariha Róisín’s Like a Bird (2020), narrativize the traumatic events in the cases of female protagonists Nomita and Taylia, mainly in the forms of repetitive dreams, gnawing guilt, depression, and self-fragmentation, due to being sexually abused by their trusted people at a very young age. While the narrativizations of the characters’ catastrophic tribulations are at the center of these novels, they also underscore the impacts of spatial locations around the characters, facilitating their survival, thus interweaving the dynamics of psychotraumatology and what is theorized as psychogeography. Hence, this study attempts to explore twofold approaches: examining the protagonists’ traumatic experiences primarily through Cathy Caruth’s formations of ‘trauma’ and ‘survival,’ supplemented with a psychogeographical reading of the novels to identify the effects of the places and walking in the protagonists’ psyches, determining their resilience henceforth. Nomita and Taylia’s experiences of sexual trauma are not merely an experience of destruction; rather, their journeys offer trauma testimony that also showcases levels of post-traumatic development through the means of psychogeographical wanderings. This article is expected to introduce a new approach to interlinking psychology and geography, mainly in the case of sexual trauma studies within South Asian settings.